Review of Islamic Law on Restrictions in the Practice of Renting a Rental Car - Bayu Anggara Syahputra; Zaenal Abidin; Kurniawan (Zabags International Journal of Islamic Studies, 2025)
The car rental business is currently being developed by business people in Indonesia. With the business of providing car rental, people can choose what car they want to use by only paying rent as happened at Zabak Travel & Rental, Talang Babat Village, Muara Sabak Barat District, East Tanjung Jabung Regency. This type of research is qualitative research with a descriptive qualitative approach. The data sources used consist of primary data sources and secondary data sources. Data collection procedures through observation, interviews and documentation. Data analysis techniques through editing, reconstruction and systematization of data. The conclusions obtained from the research results are: First, the implementation of the rental car rental agreement at the Zabak Travel & Rental car rental in Talang Babat Village contains certain requirements that must be met by all parties. Second, the review of Islamic law on the restrictions in the practice of renting a rental car at the Zabak Travel & Rental car rental in Talang Babat Village is appropriate because it fulfills the pillars and conditions mentioned in the National Sharia Council (DSN) Fatwa No. 9/DSN-MUI/2000 concerning ijarah financing. (Sighat Sewa Menyewa, namely ijab and qabul in the form of statements from both parties to the contract, either verbally or in other forms. Parties to the contract: consists of the renter/service provider and the renter/service user. The object of leasing is the benefit of the use of goods or services, which can be valued and can be implemented in the contract, as well as those that are permissible and goods must be real according to sharia provisions